Constitutional federalism in Malaysia - JF Fong (Thomson Reuters Malaysia, 2016)
This book covers constitutional history and discusses the federal system of government under the constitution, involving, inter alia, the distribution of legislative and executive powers, the ringhts and responsibilities of the federal and the state governments, the sharing of revenues, financial burdens and functions between the federal government and te states.